Biosurfactants for sustainability - Alara, Oluwaseun Ruth; Abdurahman, Nour Hamid; Ali, Hassan Alsaggaf (Academic Press, 2024)
In recent times, there have been increased discussions on environmental sustainability and protection. This has propelled the important role that biosurfactants play daily, especially the potential reutilization of treated wastes, waste reduction, and use of renewal by-products as substrates. Hence, the use of biosurfactants in different industrial sectors has increased. The production of these biosurfactants is influenced by diverse variables, including agitation, temperature, pH, and the nature of nitrogen and carbon. Most importantly, the influencing factors such as high thermal stability and pH, better surface-active properties, easy biodegradability, and nontoxicity of biosurfactants have positioned them high in quality and effectiveness above synthetic surfactants. These features have enhanced the suitability of biosurfactants in different industrial usages. These industrial sectors include pharmaceuticals, food, agriculture, and others. Besides, there is greater awareness about biosurfactants because of the increasing overall sustainability initiatives in industrial sectors. However, the advantages of biosurfactants overweigh the synthetic counterparts; nonetheless, these biomolecules have not been able to compete in terms of economy with the synthetic ones that are cheaper and readily available. Therefore, this chapter explores how biosurfactants can be sustained, the use of cheaper agro-food sources and others to allow them to compete with the existing synthetic surfactants and environmental applications for successful sustainability.